The crocodile : an extraordinary event, or a show in the arcade ... - Dostoyevsky, Fyodor, 1821-1881 (Ardis, 1985)
Tells the short story The Crocodile, about a middle class government employee who is swallowed by a crocodile in order to present the political, economic, and social theories of the author.